Air-Flow Impacting: A New Mechanochemical Method for Continuous, Highly Efficient, Large-Scale Synthesis of Metal–Organic Frameworks and Mechanistic Research - Zhao, Jun (Frontiers in Materials, 2021)
Now, the novel air-flow impacting (AFI) synthesis technology for mechanochemical synthesis of MOFs (ZIF-67) was first reported. AFI was an improvement of the traditional mechanochemical synthesis method. The results indicated that ZIF-67 was successfully synthesized after 30 min at 60 kg h-1 rates. The as-prepared ZIF-67 was characterized by fourier transform infrared spectroscopy (FT-IR), powder x-ray diffraction (P-XRD), thermogravimetric analysis (DTA/TG), scanning electron microscope (SEM), transmission electron microscope (TEM) and single-crystal x-ray diffraction. The kinetic analysis of the reaction mechanism was carried out by detecting the P-XRD patterns of the products with different reaction time. The synthesis belonged to the one-dimensional diffusion-controlled model.